CO15 | Longitudinal coagulation profiling of individuals undergoing gender-affirming hormone therapy: the hyper-gender study (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Transgender individuals appear to have an increased risk of thrombosis due to hypercoagulability associated with gender-affirming hormone therapy (GAHT). The aim of the study was to investigate the effects of GAHT on coagulation, metabolism, and erythropoiesis, and to explore the mechanisms underlying hypercoagulability in the transgender population. A better understanding of these mechanisms may help guide risk stratification and inform clinical monitoring strategies during hormone treatment.